1995
DOI: 10.1172/jci117732
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of filtration failure during postischemic injury of the human kidney. A study of the reperfused renal allograft.

Abstract: Postischemic filtration failure in experimental animals results primarily from depression of the transcapillary hydraulic pressure difference (AP), a quantity that cannot be determined in humans. To circumvent this limitation we determined the GFR and each of its remaining determinants in transplanted kidneys. Findings in 12 allografts that exhibited subsequent normofiltration (group 1) were compared with those in 11 allografts that exhibited persistent hypofiltration (group 2). Determinations were made intrao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(34 citation statements)
references
References 41 publications
0
33
0
1
Order By: Relevance
“…While an overall decrease in renal blood flow (RBF) of approximately 40%-50% has been observed in poorly functioning kidney transplant allografts (14), in many cases in animals and humans a decrease in total RBF alone cannot entirely account for the reduction in glomerular filtration rate during an episode of AKI (15,16). Of greater importance are the regional alterations in RBF that occur during AKI (13).…”
Section: Endothelium and Vascular Components Of Injurymentioning
confidence: 99%
“…While an overall decrease in renal blood flow (RBF) of approximately 40%-50% has been observed in poorly functioning kidney transplant allografts (14), in many cases in animals and humans a decrease in total RBF alone cannot entirely account for the reduction in glomerular filtration rate during an episode of AKI (15,16). Of greater importance are the regional alterations in RBF that occur during AKI (13).…”
Section: Endothelium and Vascular Components Of Injurymentioning
confidence: 99%
“…Finally, opening of tight and occluded junctions results in the unregulated paracellular movement of ions and water, thereby causing increased backleak, the third mechanism of reduced GFR following ischemic injury [39]. In an eloquent series of experiments in transplant ATN, the laboratory of Brian Myers showed that afferent vasoconstriction secondary to activation of TGF, tubular obstruction, and backleak across open tight junctions are responsible for the decrease in GFR [40][41][42]. Therefore, ischemia-induced alterations in PTCs in large part account for the reduction in GFR occurring following ischemic injury.…”
Section: Pathologymentioning
confidence: 99%
“…8 The failure in Na ϩ filtration in patients with renal allograft is due to the contraction of afferent renal arterioles with increased serum renin and endothelin I levels rather than occlusion of the renal tubules. 9 The administration of CsA in rats with ischemic renal injury accelerated the necrosis of renal tubule cells and delayed the recovery of renal function and regeneration of renal tubule tissues. 19 In the evaluation of rejection response after kidney transplantation, Doppler ultrasonography is commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…7 In the ischemic injury during kidney transplantation, the afferent arteriolar constriction by the tubuloglomerular feedback decreases the glomerular filtration rate (GFR), 8 at this time, a study reported that the serum levels of renin and endothelin I increased. 9 Angiotensin-converting enzyme (ACE) inhibitor renal scintigraphy is used widely as an effective and accurate study having a high sensitivity and specificity in the diagnosis of renovascular hypertension. The ACE inhibitor induces renal function impairment due to decreased GFR by inhibition of the production of angiotensin II, which causes renal vasoconstriction, especially in the efferent arteriole, by affecting on the renin-angiotensin system.…”
mentioning
confidence: 99%